The Impact of Gadget Addiction on Mental Health Alpha Generation - Nurlaelasari, Susan; Amanda, Yulia; Avionita, Tasya; Komalasari, Kokom; Iswandi, Dede (International Journal of Religion Education and Law, 2025)
This article discusses the factors that cause gadget addiction in children, the impact of gadget addiction on children's mental health, especially in the alpha generation, and provides strategies or solutions to overcome it. The research method used is literature study and analysis of secondary data from various trusted sources. Data was collected through a literature review which included journals, scientific articles, and research reports resulting from interviews and questionnaires. The research results show that one of the factors causing children to become addicted to gadgets is a lack of parental supervision and parenting which causes problems with the child's physical and mental health. The solution to overcome this is by limiting children's use of gadgets, one of which is by implementing a picture timetable and Google Family Link